Controlling the Coordination Sphere of Alkyllithiums Results in Selective Reactions with Allylic Amines. (6th October 2017) - Kroesen, Ulrike; Unkelbach, Christian; Schildbach, Daniel; Strohmann, Carsten
Abstract: Described herein is a selective way to control the reaction of allylic amines with metalorganic bases depending on the amine handle as well as the metalorganic base is used. Depending on the number of coordinating groups within the amine handle either a selective carbometalation or deprotonation reaction can be performed. By changing the alkali metal within the base from lithium to either sodium or potassium, a change of chemoselectivity takes place and the reaction of piperidinoallylamine can be controlled.